Pattern of maternal vaginal flora in labor and its effect on the newborn - Dr Vidya Singaravelu (Pediatric Review: International Journal of Pediatric Research, 2017)
Background: Neonatal sepsis is the most important cause of morbidity and mortality in developing countries. Early onset sepsis is attributed to abnormal bacterial colonization of the maternal urogenital tract which leads to either an ascending but silent amniotic fluid infection or symptomatic chorioamnionitis.Aims & Objectives: 1. To study the pattern of maternal vaginal flora in labor. 2. To study the outcome in the neonate.Methods: This study was conducted on 250 mothers in labor & their babies followed up till discharge in the departments of OBG & neonatology in a tertiary care medical college hospital, Deliveries by caesarean section were excluded.Results: Out of 250 mothers 130 (52%) of them showed colonization. Out of the 130 babies born to colonised mothers, 50 (38.46%) showed features of sepsis, while only 10 (8.34%) born to non-colonised mothers had features of sepsis. This study showed a statistically significant association between features of sepsis in babies and maternal vaginal colonization. Of the 60 babies with suspected sepsis, 40 had positive blood culture which is the gold standard investigation for sepsis. All of these culture positive babies i.e all 40(100%) had maternal colonization with a statistically significant association.Conclusion: This study shows that maternal vaginal colonisation has significant association with neonatal sepsis. Hence, finding the organism in the maternal vaginal flora and treating it as per sensitivity might result less cases of neonatal sepsis.